Unifying educational systems : leadership and policy perspectives - Burrello, Leonard C., 1942-; Sailor, Wayne; Kleinhammer-Tramill, Jeannie (New York : Routledge, 2013)
"Unifying Educational Systems encourages leaders to move beyond the traditional forms and rituals of leadership for special education that are caught within traditional definitions of a continuum of services. Grounded in public policy debates, research on teaching and learning, and an emerging consensus throughout the leadership community that calls into question our current practices, chapters in this volume provide a discussion of the purpose, principles, and paradoxes extant in the implementation of current special education policy. Chapter authors discuss how students are currently served, the feasibility of re-conceptualizing special education leadership in the current policy context, and the challenges for the future. Ultimately, Unifying Educational Systems calls for a new policy framework to integrate special education within the larger instructional support system in schools, in order to support a social justice and inclusive practices agenda. "--
pt. I. Introduction and the proposal for unifying systems -- pt. II. Legal and financial basis of services for a unified system -- pt. III. New conceptions of practice -- pt. IV. Leading diversity in a unified system -- pt. V. Summary and closing.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Inclusive education; Special education; Educational leadership; School management and organization; Electronic books